KOORDINASI SETTING RELAI ARUS LEBIH PADA INCOMING 2 KUDUS TERHADAP OUTGOING KUDUS 5 DAN 6 YANG MENGGUNAKAN JARINGAN DOUBLE CIRCUIT DI GI 150 KV KUDUS - Wardani, Sartika Kusuma; Subali, Subali (Vocational School Diponegoro University, 2015)
Sartika Kusuma Wardani, Subali, in paper coordination of flow over relay setting in incoming 2 kudus to outgoing 5 and 6 using double circuit network on GI 150 KV kudus explain that PT PLN make every effort to improve service to customers , one of them by increasing the reliability of the distribution of electrical energy . Reliability of the distribution network is very important for both consumers and PLN. One measure of the reliability of the system / network is a factor SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index).Â Steps that have been done one way to minimize the possibility of interference is by installing protective devices on medium voltage networks. However, installation of protection equipment is not enough if the relay setting coordination between the incoming and outgoing imprecise. In fact in recent months, an interruption in the feeder distribution network which affects the incoming relay tripnya due to failure of the feeder protection system. One of the events that have happened several times is the same disorder in a double feeder circuit (network supplied from a single source by using two networks ( two feeder ) were included in the bus and in 1 pole) and holy 5 and Â 6 which causes the incoming PMT trip. It is very risky to happen, because the resulting trip relays at all incoming feeder that gets supply voltage of the incoming. So it takes coordination of overcurrent relay settings right so that the incidence of the incoming trip Sacred 2 does not happen again . Keywords: distribution, protection, relay settings, incoming, outgoing